Website Design Using Laravel Framework for Tart Tuns Shop Sales Pontianak - Ledy Pebrianty Valenty; Sandy Kosasi; Gat Gat; David David; Susanti Margaretha Kuway (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
Websites have become a means of getting information, promotion, sales that are widely used by Indonesians. Tart Tuns has difficulties in managing orders and products because currently sales in this shop are only through Instagram, in making transactions with buyers the admin communicates via Instagram direct messages and via WhatsApp messenger. This transaction process is less efficient because the Tart Tuns cake shop must always update information about product availability on insta story. This research aims to address the existing needs of the store in the form of a website that can be used as a sales medium to be more structured and expand product offerings not limited to the store's Instagram account by utilizing the MVC architecture of the Laravel Framework and collaborative filtering algorithms. System modeling uses UML (Unified Modeling Languange) and the research method used is Design Science Research (DSR). The results of this study are to produce a sales website software at Tart Tuns using the Laravel framework which functions to help shop owners in making it easier to manage orders, products, transactions, and product categories. Suggestions from this research are that other developers can add / develop features such as product reviews, chat on the website, and product liking features.